Evaluation the scanning accuracy of blue-light laboratory scanners in complete edentulous maxilla with multiple implants with titanium scan bodies = Evaluación de la precisión de escaneado de los escáneres de laboratorio de luz azul en maxilares desdentados completos con implantes múltiples con cuerpos de escaneado de titanio - Ezmek, Bahadır
To evaluate the accuracy of complete arch scanning with multiple implant titanium scan bodies using laboratory scanners. A master model of an edentulous maxillary arch with 6 implants was fabricated. Titanium scan bodies were inserted into the model. Three laboratory scanners were used: D2000 (3Shape), Vinyl High Resolution (Smart Optics), and inEos X5 (Dentsply Sirona). The master model was consecutively scanned ten times using dental laboratory scanners (LS) without detaching and repositioning the scan bodies. Linear and angular accuracy between adjacent implants was measured using inspection software (Control X, Geomagic). The accuracy of the complete arch scans was calculated. Implant regions were defined as; parallel (R1: #24-26 and #16-14), angled (R2: #22-24 and #14-12), angled to occlusal plane (R3: #12-22), and cross-arch (R4: #16-26). The effect of LS and implant region on accuracy was compared using two-Way ANOVA (α=0.05). Significant greater linear distortion was noted in R4 (61.2±17.9μm) compared to R1 (23.4±15.5μm) and R2 (26±17.7μm) (p<0.01). Greater linear distortions were noted in R4 with D2000 (0.07±0.016 degrees) and Vinyl High Resolution (0.067±0.02 degrees) than inEos X5 (0.032±0.021 degrees) (p>0.05). Greater mean linear precisions were noted in R1 (9±8μm) and R3 (9.3±8.3μm) than R4 (12.6±10.3μm) (p<0.05). The highest linear precision was noted in D2000 (7.2±7.6μm) (p<0.05). The angular precision of D2000 (0.02±0.015 degrees) was the highest (p<0.01). The angular precision of R4 (0.036±0.018 degrees) was the lowest (p<0.01). This study revealed that the trueness was affected by the implant region and the precision was affected by both LS and implant region.